Sentinel Lymph Node in Aged Endometrial Cancer Patients “The SAGE Study”: A Multicenter Experience - Cianci, Stefano; Rosati, Andrea; Vargiu, Virginia; Capozzi, Vito Andrea; Sozzi, Giulio; Gioè, Alessandro; Gueli Alletti, Salvatore; Ercoli, Alfredo; Cosentino, Francesco; Berretta, Roberto; Chiantera, Vito; Scambia, Giovanni; et al. (Frontiers in Oncology, 2021)
Objective: The incidence of endometrial cancer is increasing in elderly people. Considering ageing progressively affects lymphatic draining function, we aimed to define its impact on IGC uptake during SLN mapping. Methods: A multicenter retrospective cohort of endometrial cancer patients with apparently early stage endometrial cancer undergoing complete surgical staging with SLN dissection was identified in four referral cancer centers from May 2015 to March 2021. Patients were classified in Group1 (< 65yo) and Group2 (≥ 65yo). The primary endpoint was the assessment of the overall, bilateral and unsuccessful SLN mapping in the two groups. Secondary outcomes were the evaluation of SLN anatomical distribution and the identification of predictors for mapping failure applying a logistic regression. Results:A total of 844 patients were enrolled in the study (499 in Group1 and 395 in Group2). The overall detection rate, the successful bilateral mapping and the mapping failure rate of the SLN were 93.8% vs 87.6% (p=0.002), 77.1% vs 66.8% (p=0.001) and 22.9% vs 33.2% (p=0.001), respectively in Group1 vs Group2. The advanced age affects the anatomical distribution of the SLN leading to a stepwise reduction of “unexpected” mapping sites (left hemipelvis: p <0.001; right hemipelvis: p =0.058). At multivariate analysis age ≥ 65 (OR: 1.495, 95% CI: 1.095-2.042, p=0.011), BMI (OR: 1.023, 95% CI: 1.000-1.046, p=0.047), non-endometrioid histotype (OR: 1.619, 95% CI: 1.067-2.458, p=0.024) and LVSI (OR: 1.407, 95% CI: 1.010-1.961, p=0.044) represent independent predictors of unsuccessful mapping. Applying binomial logistic regression analysis there was a 1.280-fold increase in the risk of failed mapping for every 10-year-old increase in age (OR: 1.280, IC 95%: 1.108-1.479, p = 0.001).A higher rate of surgical under-staging (0.9% vs 3.3%, p=0.012) and adjuvant undetreatment (p=0.018) was reported in Group2. Conclusions:Old age represents a risk factor for SLN mapping failure both intrinsically and in relation to the greater incidence of other independent risk factors such as LVSI, non-endometrioid histotype and BMI. Surgeon should target on the usual uptake along UPP during the SLN dissection in this subgroup of patients to minimize mapping failure and the consequent risk of surgical under-staging and adjuvant undertreatment.